Solutions for an augmented understanding of architecture: augmenting maps and models - Costa, F.; Gomes, Steven; Eloy, S.; Dias, J.; Mariana Lopes; Gaspar, F. (3rd SUWMIAC - Summer Workshop Microsoft-ISCTE IUL on Applied Computing, 2015)
In this presentation we will show a group of apps that were developed with the aim of assisting architects and people in general to better understand and experience architecture solutions. After a first development of a general app that explored buildings with augmented reality (ARch) , a second app was developed to augment maps in a competition context (ARch4models) and a third one to augment physical maps with more architecture information that the one present in maps (ARch4maps).